Functional Reorganization of Cortical Language Function in Glioma Patients—A Preliminary Study - Ille, Sebastian; Engel, Lara; Albers, Lucia; Schroeder, Axel; Kelm, Anna; Meyer, Bernhard; Krieg, Sandro M. (Frontiers in Oncology, 2019)
Background: Functional reorganization (FR) was shown in glioma patients by direct electrical stimulation (DES) during awake craniotomy. This option for repeated mapping is available in cases of tumor recurrence and after decision for a second surgery. Navigated repetitive transcranial magnetic stimulation (nrTMS) has shown a high correlation with results of DES during awake craniotomy for language-negative sites (LNS) and allows for a noninvasive evaluation of language function. This preliminary study aims to examine FR in glioma patients by nrTMS. Methods: A cohort of eighteen patients with left-sided perisylvian gliomas underwent preoperative nrTMS language mapping twice. The mean time between mappings was 17±12 months. The cortex was separated into anterior and posterior language-eloquent regions. We defined a tumor area and an area without tumor (WOT). Error rates (ER = number of errors per number of stimulations) and hemispheric dominance ratios (HDR) were calculated as the quotient of the left- and right-sided ER. Results: In cases in which most language function was located near the tumor during the first mapping, we found significantly more LNS in the tumor area during the second mapping as compared to cases in which function was not located near the tumor (p=0.049). Patients with seizures showed fewer LNS during the second mapping. We found more changes of cortical language function in patients with a follow-up time of more than 13 months and lower WHO-graded tumors. Conclusion: Present results confirm that nrTMS can show FR of LNS in glioma patients. Its extent, clinical impact and correlation with DES requires further evaluation but could have a considerable impact in neuro-oncology.